2012
DOI: 10.1097/pcc.0b013e3182192a6c
|View full text |Cite
|
Sign up to set email alerts
|

Targeted interventions improve shared agreement of daily goals in the pediatric intensive care unit

Abstract: Objective To improve communication during daily rounds using sequential interventions. Design Prospective cohort study Setting Multidisciplinary pediatric intensive care unit in a university hospital. Subjects The multidisciplinary rounding team in the pediatric intensive care unit, including attending physicians, physician trainees, and nurses. Interventions Daily rounds on 736 patients were observed over a nine month period. Sequential interventions were timed 8–12 weeks apart: (1) Implementing a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 21 publications
0
32
0
1
Order By: Relevance
“…They found that 75% of goals discussed on rounds and goal-related actions were documented in the medical record. Five studies suggested strategies to improve communication during rounds (27,29,(36)(37)(38). Communication Strategies.…”
Section: Health Record Use and Documentationmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that 75% of goals discussed on rounds and goal-related actions were documented in the medical record. Five studies suggested strategies to improve communication during rounds (27,29,(36)(37)(38). Communication Strategies.…”
Section: Health Record Use and Documentationmentioning
confidence: 99%
“…Cummings et al (35) reported that providing pharmacists with a mobile computer improved information retrieval, thereby reducing time required by pharmacists to access the electronic health record and increasing their availability on rounds. A standardized rounding process achieved by structured presentation and explicit definitions of each healthcare provider's role during rounds was evaluated by three studies, which showed a significant increase in healthcare provider satisfaction (36,38) and quality of discussions (27,29). Five studies suggested strategies to improve communication during rounds (27,29,(36)(37)(38).…”
Section: Health Record Use and Documentationmentioning
confidence: 99%
See 2 more Smart Citations
“…PEACE Rounds were process oriented and designed to clarify goals of treatment (Rehder et al, 2012) and whenever possible, achieve consensus. Over a twelve month period, once a week the interprofessional team met for PEACE Rounds.…”
Section: The Interventionmentioning
confidence: 99%